(untitled) (Journal of Advanced Veterinary and Animal Research, 2016)
Objective: To determine the prevalence of Schistosoma infection in cattle in Maiduguri Metropolis (MMC) and Jere Local Government Areas (LGAs) of Borno State, Nigeria. Materials and Methods: Blood samples (n=200) were collected from cattle consisting of one hundred (100) each from five (5) ward levels each of MMC and Jere LGAs. DNA samples were extracted from the serum samples, analysed and quantified using a Nano-drop machine. The extracted DNA were subjected to polymerase chain reaction (PCR). Results: The overall prevalence of Schistosoma infection was 2% (n=200). Jere LGA had 3% (n=100) while MMC had 1% (n=100). There was no statistical significant association in prevalence rate in the two LGAs studied (P=0.621) (P>0.05). At the ward levels, Custom Area in Jere LGA had 15%, Jiddari ward in MMC had 5%, and the remaining ward levels had no cases. Of the 103 female and 97 male cattle screened, the prevalence in female was 1(0.97%) and 3(3.09%) in the male. Of the 177 serum samples from above 1year (adult) examined, 4 (2.26%) were positive and none in the young. There was no statistical significant association in prevalence rate among ward levels, sex groups and age groups in the study areas (P=0.621) (P>0.05), (P=0.356) (P>0.05) and (P=1.000) (P>0.05) respectively. Of the eight (8) breeds screened, Kuri had 2.7%, Sokoto Gudali (1.82%), Abore (2%), Red Bororo (2.63%), White Fulani, Porland, Mbala and Wafara recorded no cases. The difference in prevalence rates among the breeds based on the trend of occurrence of Schistosoma infection were not significantly associated statistically (P=1.000) (P>0.05). Conclusion: There is a prevalence of Schistosoma infection in cattle in the two LGAs of Borno state. It is recommended that a system be established to maintain preventive and control programs. http://doi.org/10.5455/javar.2016.c135